Pengaruh Kepemimpinan Transformasional, Pelatihan, dan Knowledge Managemenet terhadap Kinerja Karyawan pada PT Prima Mitrajaya Mandiri - Rofik Aji Laksono; Kusuma Chandra Kirana; Eko Yulianto (Journal of Economics and Management Scienties, 2026)
The dynamics of an increasingly competitive job market require companies to continuously develop the performance of each employee to enhance success rates. Various factors can influence employee performance, including transformational leadership, training, and knowledge management. This study was conducted to identify and examine the influence of transformational leadership, training, and knowledge management on employee performance at PT Prima Mitrajaya Mandiri. This study employed a quantitative approach, with data collected through a questionnaire administered to employees. The study population comprised all 147 employees of PT Prima Mitrajaya Mandiri. Simple random sampling was used to select the sample. The sample size was determined using the Slovin formula with a 10% margin of error, resulting in 60 respondents. Data processing and analysis in this study were performed using SPSS version 26, which included tests of classical assumptions such as normality, multicollinearity, and heteroscedasticity, followed by multiple linear regression analysis, t-tests, and the coefficient of determination (R²). The study found that transformational leadership and training have a positive but insignificant effect on employee performance. Meanwhile, knowledge management has a positive and significant effect on employee performance. It is hoped that these findings will serve as a reference for management in optimizing knowledge management to improve employee performance.